The regional record of Albian oceanic anoxic events at the Apulian Platform Margin (Gargano Promontory, southern Italy) - LUCIANI, Valeria; COBIANCHI M; FABBRI S. (Revue de Micropaléontologie, 2007)
The Gargano Promontory, located on the eastern margin of the Apulia Platform, represents a distinctive Tethyan area where the transition from carbonate platform to adjacent basin is exposed on land. The Albian stratigraphic record, represented by shallow-water, slope and deep-water deposits, provides a good opportunity to investigate the regional response to oceanic anoxic events (OAEs) in different depositional settings by using an integrated, high-resolution micropalaeontological (planktonic foraminifers and calcareous nannofossils) approach. Results show that organic matter preservation is confined to the more distal areas (Marne a Fucoidi Formation), and consists of black shale intervals from the middle and late Albian (Ticinella primula/Prediscosphaera columnata Zones; upper Ticinella praeticinensis Subzone/R. achlyostaurion Zone, respectively). Integrated biostratigraphic data correlate the intervals of black shale deposition to the Urbino and Amadeus levels, previously identified and named in the Umbria-Marche Basin. These black shales record the effects of OAEs 1b and 1c. The biotic changes in the pelagic Albian succession of the Apulian Platform Margin provide evidence for episodes of eutrophication that correlate to the deposition of these black shales. Genetic models for the two episodes of organic matter preservation are proposed, taking into account both global and local controlling factors.